Votes, Clientelism, and Conditional Cash Transfer Programs: A Case Study in Brazil - Espíndola da Silva, Fábio Mariano (Politikon: The IAPSS Journal of Political Science, 2014)
Studies in the field of clientelism show that this specific social phenomenon can influence the voting patterns and local behavior in developing countries, maintaining in power a political elite that detains the vast majority of the local economic resources. Conditional Cash Transfer Programs – such as Bolsa Familia in Brazil – are designed to provide direct cash transfers from the government to the poor, in return for some conditions. Those programs represent an unexpected variable in the equation of clientelism – they provide an escape for clients from their patrons, with resources that no longer depend on the patron’s approval. This paper pursues a hypothesis that the presence of Bolsa Familia changes the vote-seeking strategies of clientelistic patrons. Despite the theoretical evidences that this should be the observed, data analysis in a case study shows that empirical evidence is inconsistent and that further research on the matter should be pursued and improved.